Rapid Changes of Body Weight after a Headstand: A Metrological Analysis - Acuña Espinoza, Alejandro (2015)
Despite recent rules from amateur wrestling sport-governing bodies intended to discourage extreme weight loss measures, wrestling culture still includes varied methods to make weight, including holding a headstand position immediately before stepping on the scale. The procedure, according to the notion, will reduce reported mass anywhere between 250 and 500g (weight between 2.45 and 4.89 N). The aim of this study was to compare any possible differences between the headstand procedure (HS) and a normal (CON) weight measure, using a metrological approach defined by the European Association of National Metrology Institutes. Seventeen adult men were weighed on a force plate before and after doing a headstand or standing normally for 30s. The order of treatment application was assigned randomly. Post-test weight was significantly larger than pre-test (mean±s.d.) (640.7 ±62.8 N and 640.3±62.7 N, respectively, p<0.0001) under both treatments. No treatment vs. time of test interaction was found. No significant difference was found between CON and HS weight (640.6±62.8 N and 640.9±62.9 N, respectively, p=0.3815). The metrological tests suggest that the statistical differences found are related to the force plate measuring errors in every pre-established time interval. The 45g (0.44 N) difference found between pretest and post-test lies within the uncertainty range identified for the equipment (±110 g or 1.08 N). In conclusion, a 30-second headstand has no significant effect on registered body weight. The small variations obtained were due to equipment-associated measuring errors. This experiment offers systematic empirical evidence to aid in the elimination of this unjustified practice among the wrestling community.